Aluminum p-type doping of silicon carbide crystals using a modified physical vapor transport growth method - Straubinger, Thomas; Bickermann, Matthias; Weingärtner, Roland; Wellmann, Peter; Winnacker, Albrecht (Journal of Crystal Growth, 2002)
We report the development of a modified physical vapor transport (PVT) growth setup for the improved aluminum p-type doping of silicon carbide (SiC) single crystals. Usually aluminum doping of SiC is carried out by adding the dopant to the SiC powder source material. However. due to aluminum source depletion a strong exponential decrease of the dopant incorporation with increasing process time is observed. In addition. often defect generation takes place due to a high initial aluminum sublimation rate. In order to improve the aluminum supply we have installed an additional gas pipe which provides a continuous flux of aluminum atoms out of an external reservoir into the growth cell. We will discuss the influence of the additional gas flow on the thermal field and mass transport inside the growth cell. Technological steps will be pointed out which were necessary to establish crystal growth with structural properties comparable to the conventional PVT process. With the modified PVT method high quality SiC single crystals with an improved axial and lateral aluminum doping homogeneity were grown (4H-SiC: 2 x 10(16) cm(-3) < p < 4 x 10(16) cm(-3) Deltap/p < 10%; 6H-SiC: 8 x 10(16) cm(-3) < p < 1.2 10(17) cm(-3). Deltap/p < 25%). (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: Doping; Growth from vapor; Semiconducting silicon compounds; modified PVT; SiC